Apresentação e Organização - Retana, Alvaro; O'Flaherty, Christian; Braga, Julião; de Sales, Leandro Melo; Granville, Lisandro Zambenedetti (Anais do Workshop Pré-IETF (WPIETF), 2017)
Apresentação do IV Workshop Pré-IETF e Mensagem dos Coordenadores do Evento.